2002
DOI: 10.1063/1.1481533
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of n-GaMnN thin films

Abstract: GaMnN thin films were synthesized using gas-source molecular-beam epitaxy. Mn concentrations between 3 and 12 at. % were investigated. No evidence of second-phase formation was observed by powder x-ray diffraction or high-resolution cross section transmission electron microscopy in films with 9% or less Mn. The films were n type as determined by capacitance–voltage or Hall analysis. Magnetic characterization performed using a squid magnetometer showed evidence of ferromagnetic ordering at room temperature for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
215
2
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(223 citation statements)
references
References 24 publications
5
215
2
1
Order By: Relevance
“…New excitement cames with the synthesis of ferromagnetic (Ga,Mn)N [6,7,8,9] with T c well above room temperature. High T c in this material was somehow expected after the predictions of Dietl et al [10], who calculated the magnetic properties of various semiconductors incorporating Mn, and concluded that wide gap semiconductors might offer better possibility for high T c .…”
Section: Introductionmentioning
confidence: 99%
“…New excitement cames with the synthesis of ferromagnetic (Ga,Mn)N [6,7,8,9] with T c well above room temperature. High T c in this material was somehow expected after the predictions of Dietl et al [10], who calculated the magnetic properties of various semiconductors incorporating Mn, and concluded that wide gap semiconductors might offer better possibility for high T c .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to synthesis of DMS having high Curie temperature at or above room temperature. Several materials have been reported to exhibit ferromagnetism in semiconductors based on IV [1], II-VI [2,3,4], and III-V [5,6,7] compounds. As a new DMS, vanadium-doped ZnSe is theoretically predicted to exhibit ferromagnetism at or above room temperature without carrier doping [8].…”
Section: Introductionmentioning
confidence: 99%
“…In samples of Ga 1−x Mn x As with selective p−doping [12] it was reported a Curie temperature T c ∼ 172K. Today it is possible to make semiconductors that are ferromagnetic at room temperature [4][5][6][7]. Several spintronic devices like spin valves, spin filters, polarizers and analyzers have been made using heterostructures including DMS [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%